Managing and Delivering Information Technology Value - Lisanti, Yuliana (Bina Nusantara University, 2011)
Investment Information Technology (IT) has always been a primary objective of the business which is expected to provide value to businesses through its role as a competitive advantage and the creation of innovation. However, it is ot easy to measure how much value is successfully created, or determine whether the IT strategy is aligned with business strategy, or find out if the IT organization has a strategy that focuses on creating business value. Innovation Value of Institute (IVI) introduces a new concept known as the IT Capability Maturity Framework (IT-CMF) which can help IT organizations to align the business vision with the IT vision so that IT strategy could focus on value creation . the IT-CMF implementation which begins with the assessment of the maturity of IT organization can provide an overall picture, so that organization can prioritize the development of appropriate IT investments to support the value creation for the overall business.